Literature Review: Strategi Konsep Arsitektur Eko-kultur pada Rancangan Rumah Layak Huni di Lahan Rawa/Gambut Kalimantan Selatan - Syaipullah, Aly; Rahman, Akbar; Febrita, Yuswinda (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
This study examines sustainable architectural design methodologies in the context of wetland environments in South Kalimantan by exploring the eco-cultural architecture framework proposed by Dedi Iskandar et al. (2025). A Design Thinking approach is adopted to formulate architectural design strategies that emphasize user-centered empathy, ecological adaptation, and the integration of local Banjar cultural values through the stages of empathize, define, ideate, prototype, and test. The findings demonstrate that the integration of ecological principles and local cultural contexts results in architectural designs that are construction-efficient, responsive to wetland conditions, and socially sustainable. This study contributes to the development of a conceptual design model for elementary schools in wetland areas, highlighting construction efficiency, environmental resilience, and the strengthening of local architectural identity in South Kalimantan.